EVALUASI KINERJA KEBERLANJUTAN PENGELOLAAN TAMAN DESA SEBAGAI ASET LINGKUNGAN DAN SOSIAL - Ilami, Ain Husnatul; Lawelai, Herman; Farid Yusuf Nur Achmad (Program Studi Administrasi Publik, 2024)
Village parks are social and environmental resources that are crucial for community welfare and have great ecological value. This research begins the cessation of management of the Syeikh Abdul Wahid Village Park in Burangasi Rumbia Village, South Buton Regency. The evaluation covers ecological and social aspects, highlighting the role of village parks in biodiversity conservation, pollution reduction and climate change mitigation. In addition, village parks serve as centers of social and cultural activity, strengthen community ties, and offer authentic tourism experiences. However, village parks face the threat of urbanization and land use changes that can disrupt their sustainability. This research uses qualitative methods with participant observation and semi-structured interviews. The results show that community involvement and village government policies play an important role in village park management, even though there are obstacles such as limited resources and funds. This evaluation aims to improve the sustainability of the village park, identify area improvements, and develop better management strategies, as well as ensuring that the village park can continue to provide long-term ecological and social benefits for the community